How can we use positron emission tomography/ computed tomography more accurately for characterization of asbestos-related pleural thickening? - Simsek, F. Selcuk; Cakmak, Muharrem; Kuslu, Duygu; Balci, Tansel A.; In, Erdal; Ozercan, Ibrahim H.; Narin, Yavuz (Termedia Publishing House Ltd, 2023)
Introduction: There is no consensus about the standardized uptake value maximum (SUVmax) cut-off value to characterize pleural thickening world-wide. Sometimes, this causes unnecessary invasive diagnostic procedures. Our first aim is to determine a cut-off value for SUVmax. Secondly, we try to answer the following question: If we use this cut-off value together with morphological parameters, can we differentiate benign thickening from ma-lignant pleural mesothelioma (MPM) more accurately? Materialand methods:Thirty-seven patientswho underwent 2-deoxy-2-fluoro-D-glucose ([18F]FDG) positron emission tomography/computed tomography (PET/CT) before pleural biopsy were included the study. All of patients had histopathologically proven primary pleural disease. Their [18F]FDG-PET/CT im-aging reports were re-assessed. If a patient's SUVmax or size of the thickening was not mentioned in the report, we calculated it with their [18F]FDG-PET/CT. Results: Age, pleural effusion, size, and SUVmax were found to have a relation-ship with MPM. We found the size > 14 mm, and SUVmax > 4.0 as cut-off values for MPM. The sensitivity, specificity, positive predictive value (PPV), and nega-tive predictive value (NPV) for size > 14 mm were found to be 86.4%, 85.2%, 82.6%, 88.5%, respectively. For SUVmax > 4.0, sensitivity, specificity, PPV, NPV were 90.9%, 87.0%, 85.1%, 92.2%, respectively. Conclusions: If a patient has SUVmax> 4.0 and/or size > 14 mm, the risk of MPM is high. These patients should undergo biopsy. If a patient's SUVmax < 4.0, size < 14 mm and does not have pleural effusion, he/she has low risk for MPM. These patients can undergo the follow-up. If a patient's SUVmax < 4, size < 14, and has pleural effusion the MPM risk is approximately 4%. These patients can undergo biopsy/cytology/follow-up. Novel studies are needed for these patients.
Keywords: mesothelioma; cut-off value; pleural thickening; 18F-FDG-PET